Synthesis of new fluorescent molecules having an aggregation-induced emission property derived from 4-fluoroisoxazoles - Sato, Kazuyuki; Kawasaki, Akira; Karuo, Yukiko; Tarui, Atsushi; Kawai, Kentaro; Omote, Masaaki (Beilstein Journal of Organic Chemistry, 2020)
Fluorescent molecules based on a fluorinated isoxazole scaffold were synthesized and investigated for their photochemical properties. The introduction of a fluorine substituent into 3,5-diarylisoxazoles led to an increase of fluorescence intensity and exhibited a redshift in the emission intensity. α-Fluorinated boron ketoiminates (F-BKIs) were also synthesized via a ring-opening reaction of 4-fluoroisoxazoles and exhibited highly fluorescent luminescence and aggregation-induced emission (AIE), showing promise as a new fluorophore.
Keywords: aggregation-induced emission; boron ketoiminates; fluorescent probe; α-fluorinated boron ketoiminates; 4-fluoroisoxazoles